The political economy of Austria - Arndt, Sven W.; American Enterprise Institute for Public Policy Research; Austrian Institute (New York, N.Y.) (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1982)
It presents the edited proceedings of a conference sponsored by the American Enterprise Institute and the Austrian Institute which evaluates the Austrian's economy accomplishments in dealing with challenges similar to those faced elsewhere and the institutional arrangements that made the possible.
Proceedings of a conference in the early autumn of 1981 sponsored by the Austrian Institute in New York and the American Enterprise Institute.
Includes bibliographical references.
occ 15/01/2019
Loans
Keywords: Economic policy; Addresses,essays, lectures; Political economy; Austria